Water Purification Process Uses Adsorbents From Natural - Lailatul Fadhilah; Jasmidi Jasmidi; Rini Selly; Moondra Zubir (Indonesian Journal of Chemical Science and Technology (IJCST), 2021)
Adsorbent is an adsorption that is used to absorb various pollutants. Adsorbents can be used from natural materials. Natural ingredients that can be used are oil palm empty bunches. Oil palm empty bunches are a carbon-rich material that is getting new research interest in adsorption because of its abundance and properties. Oil palm empty bunches contain carbon, nitrogen, hydrogen, oxygen, sulfur, lignin, hemicellulose, and cellulose. Oil palm empty bunches are used as adsorbent for water saturation.